EVALUASI TINGKAT KEPUASAN PELAYANAN KEFARMASIAN PADA PASIEN BPJS RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH RATU ZALECHA MARTAPURA DENGAN MENGGUNAKAN METODE CUSTOMER WINDOW QUADRAT (CWQ) - Napisah, Siti; Muthaharah, Mustika; Mulyani, Tuty; Wulandari, Putrie; Wirahadikesuma, Ikhwan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Patient satisfaction assessment is a consumer response to the services provided according to the needs and expectations of patients towards pharmaceutical services. The purpose of this study was to determine the level of satisfaction with pharmaceutical services in outpatient BPJS patients at RSUD Ratu Zalecha Martapura and to determine the dimensions that affect the quality of pharmaceutical services that will be improved for patient satisfaction using the customer window quadrat method. The type of quantitative research with a descriptive cross-sectional design with a purposive sampling technique. The results of this study indicate that the level of satisfaction in each quality dimension is Tangible 92.73 (very satisfied), Responsiveness 87.63 (very satisfied), Reliability 90.83% (very satisfied), Assurance 87.58% (very satisfied), Empaty 95.71% (very satisfied). Based on the results of the CWQ analysis, there is 1 statement item that is the main priority in the improvements that must be made by the pharmacy, namely in quadrant A. The priority for improvement in item 2